Optimalisasi Kader Usaha Kesehatan Sekolah dalam Penanganan Kegawatdaruratan di Sekolah: Optimization School Health Service of Managing Emergencies Occurring at School - Trifianingsih, Dyah; Sitompul, Dania Relina; Unja, Ermeisi Er (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
School infirmary (UKS) is a forum for organizing programs that provide health services to students at school, especially in emergency cases before receiving further services. Emergencies require fast and precise treatment. For this reason, health education and education programs are needed in schools, especially in providing emergency treatment to UKS cadres. Community service activities aim to increase the knowledge and skills of UKS cadres in providing emergency care that occurs in schools and providing optimal health services in schools. The method used in this community service is lectured in the form of health education through counseling and demonstrations related to first aid measures for emergency cases that can occur at school, such as fainting, wounds and bleeding, broken bones, and cardiac arrest. Community service activities will be held on July 2 2024 with the target of the activity being Nahdatul Ulama Middle School students and UKS cadres. Community service activities begin with a lecture related to the concept and handling of everyday emergencies that might occur at school, followed by a demonstration of handling techniques, as well as questions and answers. Evaluation is carried out by giving questionnaires at the beginning (pre) and end (post) to participants. As well as a re-demonstration of the first actions for handling emergency cases.